The Power of Parasocial Interaction: Relatability, Trust, and Ethical Engagement in Gen Z Influencer Marketing - Lestari, Putri Ayu; Islami, Nafa Aqla (Communica : Journal of Communication, 2024)
As short-form video platforms gain prominence, influencer marketing increasingly depends on parasocial interactions (PSI) to engage Generation Z consumers. The aim of this study is to examine the extent to which influencer relatability and trust influence purchase intention, with PSI serving as a mediating mechanism. Using survey data from 400 Indonesian urban Gen Z users active on Instagram Reels, TikTok, and YouTube Shorts, we conducted SEM analyses to validate the mediation effect of PSI. Model fit indices (CFI > 0.90, RMSEA < 0.08, SRMR < 0.08) confirmed acceptable fit, with indirect effects indicating significant emotional mediation pathways (β = 0.24, p < 0.01). This study is novel in highlighting the combined role of relatability and trust within the short-form video ecosystem, specifically in a Southeast Asian Gen Z context. Results demonstrate that emotionally resonant storytelling and interactive content (e.g., Q&A sessions, live streams) enhance PSI, which in turn strengthens consumer trust and brand loyalty. In practical terms, the findings suggest that brands should adopt authentic engagement, ethical transparency, and adaptive multi-platform strategies to sustain long-term relevance. However, authenticity and ethical transparency remain critical, as Gen Z is highly sensitive to manipulative content and commercial overreach. This research contributes theoretically by validating PSI as a mediating mechanism in influencer marketing, while providing practical guidance for industry players seeking to design ethical and effective campaigns.